Study of the variable (NI) in Manaus-Brazil: data treatment with r - Rodrigues, Tatiana Bermond dos Santos (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
The variable (nj) is present in paroxytone words ending in –nia and – nio in Brazilian Portuguese. Some variants for this variable were registered by Cruz (2004) in her research in the countryside of Amazonas. Rodrigues (2014) started research on this variable among the speakers in the capital city, Manaus, looking for some evidence of a strong palatalization process, as a pre- analysis carried out in 2014 indicated. The aim of this paper is to present a second data analysis carried out as part of a Sandwich Phd Program, which should result in the quantitative analysis of this linguistic variation. The methods used in this paper involved acoustic analysis with formant measurements and spectrographic cues and quantitative data treatment with R Software.